Therapeutic Potential of Targeting Malt1-Dependent TCR Downstream Signaling to Promote the Survival of MHC-Mismatched Allografts - Govender, Lerisa; Mikulic, Josip; Wyss, Jean-Christophe; Gaide, Olivier; Thome, Margot; Golshayan, Dela (Frontiers in Immunology, 2020)
Strategies targeting T cells are the cornerstone of immunosuppression after solid organ transplantation. The transcription factor NF-κB is a key regulator of downstream T-cell activation and induction of inflammatory mediators; its full activation via antigen receptor engagement requires both the scaffold and the protease activity of the paracaspase Malt1. Recent studies have highlighted that Malt1-deficient mice were resistant to experimental autoimmune encephalomyelitis, although they lacked peripheral regulatory T cells (Treg). Here, we compared targeting Malt1 versus using calcineurin inhibitors as immunosuppression in a stringent experimental transplantation model. We found that Malt1-deficiency impaired Th1-mediated alloresponses in vitro and in vivo and significantly prolonged MHC-mismatched skin allograft survival, compared to cyclosporine. However, it paradoxically enhanced Th17 differentiation in the transplantation setting. Interestingly, more selective inhibition of Malt1 protease activity in wild-type mouse and human T cells in vitro led to attenuation of alloreactive Th1 cells, while preserving preexisting Treg in the peripheral T-cell pool, and without promoting Th17 differentiation. Thus, there is a place for further investigation of the role of Malt1 signaling in the setting of transplantation.